Pengaruh Viral Marketing dan Internet Celebrity Endorsement terhadap Impulse Buying Melalui Online Trust - Bisma, Reindra Prasista; Hadi, Effed Darta (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to examine the impact of viral marketing and internet celebrity endorsement on impulsive buying behavior through online trust in the context of the Erigo brand. The study utilizes primary data and adopts a quantitative approach with purposive sampling techniques. The study's population includes all consumers who have purchased Erigo products in the city of Bengkulu, totaling 130 respondents. Structural Equation Modeling - Partial Least Squares (SEM-PLS) version 4.0 is employed as the research method. The research findings indicate that viral marketing and internet celebrity endorsement have a positive and significant impact on online trust. However, it was observed that the effect of viral marketing on impulsive buying behavior is not statistically significant, and internet celebrity endorsement has a non-significant negative influence on impulsive buying behavior. Furthermore, the study reveals that online trust has a positive and significant impact on impulsive buying behavior. Additionally, the research results demonstrate that both viral marketing and internet celebrity endorsement significantly influence impulsive buying behavior through the mediator of online trust.